Trombosis venosa profunda en paciente de 27 años más embarazo de 30 semanas - Zambrano Loor, Diana Jessenia (2018)
The incidence of venous thromboembolism (VTE) in pregnancy increases approximately 5 to 10 times more compared to non-pregnant women, due to the modifications that the pregnancy itself produces on the factors of coagulation and fibrinolytic systems. It is estimated that VTE complicates between 1 per 1000 pregnancies. During pregnancy, maternal haemostasis is characterized by being a prothrombotic state in which changes occur in the hemostatic system, with the aim of preventing possible bleeding during implantation, delivery and placentation. Adaptation of the haemostatic system in pregnancy predisposes women to deep vein thrombosis in combination with other factors such as multiparity, obesity, advanced maternal age, history of previous thromboembolism. We present the case of a 27-year-old patient, who came to the general hospital Martin Icaza due to emergencies with four clinicians, edema in the lower extremity of the left side, pain in the hypogastric of slight intensity and difficult walking, oriented in time and space, at the moment the signs of normal vital, by means of the physical exploration the doctor entered it with presumptive diagnosis of venous thrombosis plus pregnancy of 30 weeks and proceeds to the accomplishment of the complementary examinations. The treatment of best choice is low molecular weight heparin for the reason that can not cross the placental barrier, has a better safety profile as it is effective and easy to administer, side effects such as thrombocytopenia, osteoporosis and osteopenia